Peran Brand Loyalty Sebagai Mediator Antara Brand Love Dan Brand Trust Konsumenusaha Jasa Perjalanan Wisata - Sri Vandayuli Riorini (Jurnal Manajemen, 2017)
Competition in tour & travel in gaining subscribers is increasing in line with the increment of consumer demand for traveling. Brands can be a competitive tool of a company. Research conducted is aimed at analyzing Brand Love, Brand Trust toward the Word of Mouth through Brand Loyalty. A total of 200 respondents in the sample who use the services of tour and travel is selected by using Purposive sampling technique. The method of data analysis applies the Structural Equation Model / SEM. This study finds (1) the positive and direct influence of Brand Love, Brand Trust toward Brand Loyalty, Word of Mouth. (2) Brand Loyalty plays a role in mediating the relationship between Brand Love, Brand Trust with Word of Mouth. (3) The strongest factor affecting the Word of Mouth is the Brand Trust. For further research is recommended to include Brand Commitment as antecedent of Brand Loyalty, and to apply this research to other services categories.